2008
DOI: 10.1897/08-112.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bacterial community structure associated with coastal copper enrichment

Abstract: Marine bacterial communities isolated from the water column, sediment, the rock surface, and the green seaweed Ulva compressa were studied in an intertidal ecosystem. The study area included a coastal zone chronically affected by copper mine waste disposals. Bacterial community composition was analyzed by terminal restriction fragment length polymorphism (T-RFLP) of 16S rRNA genes, and multivariate analyses of T-RFLP data sets were used for comparisons. Results showed that diversity and richness indexes were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…This zone is essentially free of other pollutants [18]. Mean total Cu concentration found in these sediments (1,054 mg/kg) is much higher than levels associated with noncontaminated sediments, being approximately 30 times greater [32].…”
Section: Caleta Palito: High Copper Concentrationsmentioning
confidence: 84%
See 2 more Smart Citations
“…This zone is essentially free of other pollutants [18]. Mean total Cu concentration found in these sediments (1,054 mg/kg) is much higher than levels associated with noncontaminated sediments, being approximately 30 times greater [32].…”
Section: Caleta Palito: High Copper Concentrationsmentioning
confidence: 84%
“…Values of R ! 0.5 account for high differences, whereas between 0.25 and 0.5 differences are considered as moderate [18].…”
Section: Polymorphism Reactions Data Handling and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, metagenomics is currently being used to monitor the impact of anthropogenic activities on coastal microbial composition. Port et al [60] found an increase in antibiotic resistance genes caused by coastal eluent discharges, while Morán et al [61] showed signiicant changes in bacterial community structures caused by coastal copper disposal in La Lancha and Chañaral bay in the Paciic Ocean. Overall, these studies show that metagenomics is not only used to identify novel pathogens, but it is also used to monitor the impact of human activities on microbial composition in diferent aquatic environments.…”
Section: Monitoring Of Environmental Microbiomesmentioning
confidence: 99%
“…Rochester, NY, USA). The liquid was centrifuged for 15 min at 18 000 g, and the pellet was re-suspended in 200 ul of 1X TBE buffer (Moran et al, 2008;Gharaibeh et al, 2009;Gantner et al, 2011;Medinger et al, 2010). Ready-Lyse ™ Lysozyme (Epicentre Technologies, Madison, USA) was used to lyse the cell, and DNA was extracted and purified using either a DNAeasy kit (Qiagen, Toronto, Canada) or a Master Pure DNA purification kit (Epicentre Technologies, Madison, USA) according to the manufacturer's instructions.…”
Section: Pyrosequencingmentioning
confidence: 99%